Comparing Colon Capsule Endoscopy To Colonoscopy; A Symptomatic Patient?s Perspective - Mc Namara, Deirdre (My University, 2022)
Background Colon Capsule Endoscopy (CCE) has proven efficacy in a variety of gastrointestinal diseases. Few studies have assessed patient-reported outcomes and preference between colonoscopy and CCE. Methods Patients from our centre who had both a CCE and colonoscopy within a 12-month period were identified. We performed over-the-phone interviews focused on satisfaction, comfort, and overall preference with a 10-point Likert scale. Electronic records were reviewed; reported Modified-Gloucester-Comfort-Scale (GCS) score, sedation, bowel preparation and endoscopist grade were documented. Data was compared between procedures. A Fishers exact test was used to compare proportions and a Student t-test was used to compare means, a p < 0.05 was considered significant. Results In all, 40 patients were identified, 57.5% (23/40) were female and the mean age was 48 years (24–78). All patients were referred for investigation of lower gastrointestinal symptoms as part of an ongoing study [Endosc Int Open. 2021;09(06):E965–70]. There was a significance difference in mean comfort (9.2 vs 6.7, p < 0.0001, 95% CI − 3.51 to − 1.44) but not satisfaction (8.3 vs 7.7, p = 0.2, 95% CI − 1.48 to 0.33) between CCE and colonoscopy. Main cause of dissatisfaction with CCE was bowel preparation and for colonoscopy was discomfort. Age and gender were not found to be variables. The correlation between GCS and patient reported values was weak (R = − 0.28). Overall, 77.5% (31/40) of patients would prefer a CCE if they required further bowel investigation. Of these, 77.4% (24/31) preferred a CCE despite the potential need for follow-up colonoscopy. Conclusions CCE has a high satisfaction rating (8.3 vs 7.7) and has a higher patient reported comfort rating (9.2 vs 6.7) than colonoscopy. Studies have confirmed CCE and colonoscopy have equivalent diagnostic yields. The majority of patients in our cohort prefer CCE to colonoscopy. CCE should be considered as an alternative to colonoscopy in selected individuals.
PUBLISHED
Keywords: Colon Capsule Endoscopy; Colonoscopy; Patient preference; Comfort; Capsule Endoscopy; colon capsule endoscopy; Health